2018
DOI: 10.1007/s00276-018-1977-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and histological study of the deep neck fasciae: does the alar fascia exist?

Abstract: The alar fascia is a layer of the cervical neck fascia connected with the visceral fascia from C1 to T2 levels. The anatomical limits of this alar fascia and its relationships with the internal carotid artery are important in the surgical management and the prognosis of deep neck infections and retropharyngeal lymph node metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 14 publications
2
34
1
1
Order By: Relevance
“…Feigl (2015) called the alar fascia 'fascia intercarotica' because it crosses the median plane from the left carotid sheath to the right one. Recently, Gavid et al (2018) confirmed these results, as shown in fig. 4 of their article.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Feigl (2015) called the alar fascia 'fascia intercarotica' because it crosses the median plane from the left carotid sheath to the right one. Recently, Gavid et al (2018) confirmed these results, as shown in fig. 4 of their article.…”
Section: Discussionsupporting
confidence: 58%
“…Scali et al (2015) asserted that the alar fascia could not be identified above the level of C1; the superior limit of the alar fascia was the horizontal plane passing through the superior limit of the posterior tubercle of the atlas. Gavid et al (2018) found that the alar fascia extended from C1 to T2. For Standring (2016), the alar fascia extends inferiorly from the cranial base to about the level of C7 (varying between C6 and T4).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations